1988
DOI: 10.1002/ar.1092200402
|View full text |Cite
|
Sign up to set email alerts
|

Human intervertebral disc: Structure and function

Abstract: This review begins with a brief introduction in which the development, blood supply and innervation of the intervertebral disc is considered, particularly as these may influence the following sections on structure and function. The three regions within the disc--that is, the nucleus pulposus, annulus fibrosus, and cartilage end plates--are considered in some detail. There appears to be no distinct border between the central nucleus pulposus and the outer annulus fibrosus, the main difference being in their fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
358
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(374 citation statements)
references
References 103 publications
2
358
1
3
Order By: Relevance
“…Better connectivity was observed at the IVD-VEP and IVD-CEP junctions than between the CEP and VEP where, at the IVD-CEP interface in particular, good fibre integration was seen, concurring with previous findings at these interfaces [17], [13], [12], [27]. Due to the presence of the epiphyseal ring in human spines, there are fibres from the outer AF continuing into the VEP, whilst those at the inner AF continue into the CEP.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Better connectivity was observed at the IVD-VEP and IVD-CEP junctions than between the CEP and VEP where, at the IVD-CEP interface in particular, good fibre integration was seen, concurring with previous findings at these interfaces [17], [13], [12], [27]. Due to the presence of the epiphyseal ring in human spines, there are fibres from the outer AF continuing into the VEP, whilst those at the inner AF continue into the CEP.…”
Section: Discussionsupporting
confidence: 88%
“…Failure at the interface between the IVD and VEP appears to be a main contributor in the aetiology of herniations [33], [25], [38], with endplate being present in almost 50% of herniated disc tissue [20], but structural integrity at this junction has not previously been investigated in the aetiology of disc degeneration Several studies report clear integration between the IVD and CEP, with collagen fibres running seamlessly between the two tissues [17], [13], [12], [27]; a recent study by Herrero et al [11] focussed on non-degenerate human spines and showed that integration at the CEP-VEP junction changes with age and with spinal level. It is well recognised that, at the outer annulus fibrosus (AF), fibres are continuous from the IVD to the VEP [14], but integration at the CEP-VEP interface remains questionable, with some proposing that it is present [12] and others that it is not [27], [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical fixation in this extended state followed by decalcification then enabled us to show microscopically and ultrastructurally the existence of discrete nodal insertions into the cartilaginous endplate and confirmed the existence of actual structural integration between the nucleus and endplate. These findings contrast with the more widely held view that the inner nucleus is a largely unstructured gelatinous substance which possesses little or no structural cohesion with its surroundings [3][4][5].…”
Section: Introductioncontrasting
confidence: 91%
“…It is composed of several connective tissues of dissimilar composition and structure and it is the dynamic interplay between these in the biocomposite IVD which equips it with its unique biomechanical properties and ability to act as a viscoelastic and hydrodynamic weight bearing cushion absorbing and dissipating axial spinal compressive loads [5,7,16,22,40,49,50]. The outermost region of the IVD, the annulus fibrosus (AF) is composed of collagenous lamellae which convey tensile properties and along with the superior and inferior hyaline-like cartilaginous endplates, prevent the inner proteoglycan rich region of the IVD, the nucleus pulposus (NP) being extruded anteriorly or posteriorly during axial and torsional spinal loading.…”
Section: Introductionmentioning
confidence: 99%